Refractory celiac disease and its mimickers: a review on pathogenesis, clinical-pathological features and therapeutic challenges - Scarmozzino, Federico; Pizzi, Marco; Pelizzaro, Filippo; Angerilli, Valentina; Dei Tos, Angelo Paolo; Piazza, Francesco; Savarino, Edoardo Vincenzo; Zingone, Fabiana; Fassan, Matteo (Frontiers in Oncology, 2023)
Refractory celiac disease (RCD) and enteropathy-associated T-cell lymphoma (EATL) are rare, yet severe complications of celiac disease (CD). Over the last decades, several studies have addressed the biology and clinical-pathological features of such conditions, highlighting unique disease patterns and recurrent genetic events. Current classification proposals identify two forms of RCD, namely: (i) type 1 RCD (RCD-I), characterized by phenotypically normal intra-epithelial lymphocytes (IELs); and (ii) type 2 RCD (RCD-II), featuring phenotypically aberrant IELs. While RCD-I likely represents a gluten-independent dysimmune reaction against small bowel epithelial cells, RCD-II is better considered an in situ aggressive T-cell lymphoma, with high rates of progression to overt EATL. The diagnosis of RCD and EATL is often challenging, due to misleading clinical-pathological features and to significant overlap with several CD-unrelated gastro-intestinal disorders. Similarly, the treatment of RCD and EATL is an unmet clinical need for both gastroenterologists and hematologists. Moving from such premises, this review aims to provide a comprehensive view of RCD and EATL, specifically considering their pathogenesis and the many still open issues concerning their diagnosis and clinical management.